Pulmonary hamartoma in a patient operated on for a colon neoplasm - Davidenko, Nicolás; Carzoglio, Joaquín; Berazategui, Ruver; Müller, Augusto; Toledo, Nancy; Delgado, Bolívar (Cirugía del Uruguay, 1986)
Observation o! a single pulmonary hamartoma in a patient having recently (11 months) been operated of a colon carcinoma. Presence of a lung nodule suggested the existence of secondarism, the more so because growing had been detected at a rate of 0,5 cm in diameter, in a period of seven months. Computed tomography did not provide the etiological diagnosis because there is very little experience in this subject the world over, though in pulmonary hamartoma there are present pathognomonic signs when associated with calcification and fatty tissue. Upon presumption of a single pulmonary secondarism, upper right lobectomy was performed. Pathological anatomy provides the definitive diagnosis.